Impact of Regional Location and Territorial Characteristics on Profitability in the Spanish Pig Farming Industry - Alba Cardil; José Luis Gallizo; Manuel Salvador (Agriculture)
This work aimed to identify the locational, territorial and financial characteristics that impact the profitability of companies in the Spanish pig sector. The data were extracted from the SABI database, which contains economic and financial information. A sample of 1247 Spanish companies (14,254 observations) was obtained, providing an unbalanced panel dataset for the 2004–2018 period. The statistical analysis considered factors that potentially influence the profitability of companies, considering the potential existence of endogeneity issues among some of the variables analyzed. Companies tended to be located in autonomous communities in inland areas, which had higher depopulation rates and shorter average distances from companies to feed mills and slaughterhouses. There was regional specialization, which was influenced by the ability to invest in infrastructure, proximity to the markets, farm size and efficiency in resource management, which had a positive influence on profitability. These factors led to differences between regions, together with the support of public administration for companies that invest in sparsely populated areas. The results obtained will be of interest to policymakers developing measures aimed at providing better access to inputs through proximity to feed mills and slaughterhouses, as well as to new entrepreneurs in the sector who want to establish their businesses in the most specialized regions.